A função da ritmicidade para a constituição psíquica e suas implicações na clínica psicanalítica com crianças - Brito, Kemylle Mesquita (2023)
The present research has as its theme an investigation into the function of rhythmicity for the psychic constitution and its possible implications in the clinic with children, based on the experience in offices mediated by music, as an extensionist for the Clínica Aesthetics and Politics (CEP) of Care program. The question regarding the role of rhythmicity in the psychic constitution and its relationship with the psychoanalytic clinic with children triggers this study and reverberates in questions about the primary processes of symbolization. We used the report of workshops mediated by music in a Basic Health Unit, in the pandemic context, considering the theoretical-clinical references of psychoanalysis. The research used the clinical-qualitative method, which aims to investigate problematizations that arise from clinical listening to construct the research object. Initially, we investigated the concept of rhythmicity, proposing to locate possible paths for its elaboration in Freud, mainly with texts that are based on metapsychological studies. We delve into historical questions raised by authors such as Winnicott, Lacan and contemporary authors, regarding rhythm and object relations, safeguarding the epistemological differences called into question. Thus, in a third moment, the experience with offices mediated by music was related, as a bet on promoting care in Basic Health Care, in working with children in institutions. Therefore, the research is situated in the field of dialogue between the institutional psychoanalytic clinic with children with serious psychological suffering and the musical experience.